2000
DOI: 10.1097/00008469-200008000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of carcinogen-induced mouse skin papilloma by whole fruit aqueous extract of Momordica charantia

Abstract: The anticarcinogenic effect of aqueous extract of fruit of Momordica charantia (bitter gourd), which is widely used as a vegetable in India, was studied in a two-step skin carcinogenesis model in mice. The possible mode of action was also investigated. Oral administration of the fruit extract was found to have an adverse effect on the general health and lifespan of the animals when used at a high concentration. But when this dose was reduced by half, the test extract afforded protection from the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 15 publications
0
37
0
2
Order By: Relevance
“…Moreover, elevated levels of serum cholesterol and triglycerides in hyperlipidemic, diabetic, or insulin-resistant rodents were shown to be suppressed by BME [189][190][191][192], which is consistent with the clinical hyperlipidemic impact of metformin [193][194][195][196]. On the other hand, BME was demonstrated to possess an antipromotional effect on cancer induction in rodent models of either spontaneous or carcinogen-induced carcinoma [170,197,198]. Coincidently, metformin's fellow biguanide, phenformin, has also been revealed to exert similar effects by downregulating IGFI activity [185,199].…”
Section: Nutraceuticals and Traditional Medicinesmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, elevated levels of serum cholesterol and triglycerides in hyperlipidemic, diabetic, or insulin-resistant rodents were shown to be suppressed by BME [189][190][191][192], which is consistent with the clinical hyperlipidemic impact of metformin [193][194][195][196]. On the other hand, BME was demonstrated to possess an antipromotional effect on cancer induction in rodent models of either spontaneous or carcinogen-induced carcinoma [170,197,198]. Coincidently, metformin's fellow biguanide, phenformin, has also been revealed to exert similar effects by downregulating IGFI activity [185,199].…”
Section: Nutraceuticals and Traditional Medicinesmentioning
confidence: 58%
“…Over the years, BME has already drawn global attention due to its increasing and valuable medicinal values. Apart from its amazing hypoglycemia action, previous findings from independent laboratories have revealed that constituents of bitter melon can have analgesic, antioxidant, anticancer, antiviral, antimutagenic, abortifacient, cytotoxic, and immunomodulating properties [168][169][170]. Lots of BME dietary supplement products are currently available and marketed in numerous health food stores worldwide.…”
Section: Nutraceuticals and Traditional Medicinesmentioning
confidence: 99%
“…Different parts of these plants have been used in the Indian system of medicine for a number of ailments besides diabetes. 9,10) Our previous experimental results were highly encouraging as they revealed that blood glucose level was significantly lowered after oral administration of aqueous extract of Momordica charantia seeds in glucose load condition and in streptozotocin induced diabetes. 11) In view of the above considerations, the present study was designed to examine the effect of an aqueous extract from the seeds of Momordica charantia on oxidative stress in plasma and pancreas of diabetic rats induced by streptozotocin, and their efficacy was compared with glibenclamide, a standard hypoglycemic drug.…”
Section: )mentioning
confidence: 90%
“…Various preliminary studies (in vitro as well as in vivo) with crude MC extract and its various purified fraction-including MAP 30-have shown anticancer activity against lymphoid leukemia, lymphoma, choriocarcinoma, melanoma, breast cancer, skin tumor, prostatic cancer, squamous carcinoma of tongue and larynx, human bladder carcinomas and Hodgkin's disease (Licastro et al, 1980;Ng et al, 1994;Battelli et al, 1996;Ganguly et al, 2000;Sun et al, 2001;Basch et al, 2003;). However, Kusamran et al (1998) demonstrated chemopreventive potential of Thailand Momordica charantia but not by the Chinese variety.…”
Section: Anticancer Activitymentioning
confidence: 99%